Special paperStroke caused by carotid artery dissection during ablation of atrial arrhythmia - Raczak, Maciej; Lasek-Bal, Anetta; Hoffmann, Andrzej; Mizia-Stec, Katarzyna; Czapska, Anita; Wnuk-Wojnar, Anna M. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
A 55-year-old woman was admitted to the Cardiology Department due to a poorly tolerated attack of tachyarrhythmia. The patient was enrolled in the electrophysiology study (EPS) study with radiofrequency ablation (RF). After a few applications, during transseptal puncture, the patient demonstrated a neurological syndrome in the form of progressive aphasia and weakness in the right extremities. Computed tomography angiography showed dissection of the left common carotid artery and internal carotid artery with a thrombus within their lumen. Intravenous thrombolytic therapy was initiated, which resulted in an improvement in the patient’s neurological status.